Proteomics Profiling and Inflammatory Factor Gene Expression in LPS-Stimulated RAW 264.7 Cells Treated with Crocodylus siamensis Hemoglobin - Nisachon Jangpromma (Science Faculty of Chiang Mai University, 2019)
Although we previously reported that Crocodylus siamensis hemoglobin (cHb) exhibits anti-inflammatory properties by suppressing nitric oxide (NO) production, the actual underlying mechanism has yet remained elusive. Consequently, this report represents the first study aimed to shed light upon the basic mechanistic details of the anti-inflammatory activities of cHb. In the present study, both 100 and 200 mg/ml of cHb were found to reduce the production of NO in LPS-stimulated RAW 264.7 cells. Consistent with the NO testing results, it was observed that co-treatment with cHb also significantly decreased inducible nitric oxide synthase (iNOS), likely due to decreased expression levels of cyclooxygenase-2 (COX-2) and pro-inflammatory cytokines, such as interleukin (IL)-1b and IL-6 mRNA. Therefore, these results indicate that the mechanism of cHb-induced decrease of NO production might be associated with the transcriptional suppression of iNOS. Moreover, the expression of heme oxygenase-1 (HO-1), an anti-inflammatory enzyme, was evaluated in more detail. It could be shown that HO-1 levels were increased in RAW 264.7 cells co-treated with cHb in a concentration-dependent manner. To elucidate the proteomics response of macrophages treated with LPS in the presence or absence of cHb, several proteins with differential expressions were identified via LC-MS/MS analysis. With respect to the individual functions of these proteins, our data indicated involvement in various processes during inflammation, such as cellular metabolism, protein fate, oxidative burst, signal transduction and morphogenesis. Consequently, all results of this study directly indicate that cHb exhibits anti-inflammatory activity on LPS-stimulated RAW 264.7 cells via functioning as an activator or suppressor in the expression of inflammatory factor genes and affects several specific proteins related to important pathways of inflammation.